Ocena poziomu atrakcyjności turystycznej powiatów województwa wielkopolskiego - Witkowska, Aleksandra; Witkowski, Marek (The Level of Touristic Attractiveness in Districts in Wielkopolska Province, 2009)
In analysis below, a touristic attractiveness of districts in Wielkopolska province was appraised. For that, we used three main attributes, which describe that attractiveness: touristic values, transport availability and infrastructure. These attributes were represented by seven diagnostical variables and we used the discriminating function, which had not been used earlier in such a research. The results showed that the most attractive districts in given period of time were: the city of Poznań, the city of Leszno and Międzychodzki district. The lowest attractiveness was noted in the city of Konin and in Turecki and Grodziski district. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 460-468